If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 71 = 156 Reorder the terms: 71 + 25x = 156 Solving 71 + 25x = 156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-71' to each side of the equation. 71 + -71 + 25x = 156 + -71 Combine like terms: 71 + -71 = 0 0 + 25x = 156 + -71 25x = 156 + -71 Combine like terms: 156 + -71 = 85 25x = 85 Divide each side by '25'. x = 3.4 Simplifying x = 3.4
| 4(7x+8)+x=206 | | 2t=lb | | 6r=60 | | 3x+1+58x+33x=115 | | 75s=195 | | 2(-3)+2(-1)-(-3)(-1)+21= | | 3x+1+58x+13x=115 | | x(9+8)=33 | | =11.6 | | Y/3-3=-11 | | 12x+3=3(2x+6) | | 405.36=230+0.64x | | u+6u=14 | | -9+3v=v+3 | | x-3=-3-10x+7x | | -13+5x=x-1 | | 10n+15=9n+6n | | (3x^3/z)^3 | | 6x+21=7(x+3) | | 1-4k=-5k-1 | | -6-a=1+6a | | 5x-3=10x | | -5k+10k+16=1+2k | | -12x-14=-74 | | 5(8+7c)=390 | | 3x+15x+7=162 | | 7a-2=10+7a+4a | | 3/5x-2/3 | | 3/5x-2/5 | | -2+5v=9v+10 | | 12-9b=6-8b | | 2u+8u-5u= |